Application for USAID/BHA award. Food vulnerability reduction in la Gonave. Phase II – PREVAG 2 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2024)
The Inter-American Institute for Cooperation on Agriculture (IICA) has submitted an application to USAID/BHA for the project "FOOD VULNERABILITY REDUCTION in La Gonave, Haiti, Phase II - PREVAG 2." The application outlines proposed interventions, which include enhancements to agricultural production and unconditional food assistance to address food insecurity on the island. Emphasis is placed on the importance of involving women in decision-making processes, and the need for monitoring and feedback to ensure the project's success is mentioned. The island of La Gonave faces economic, environmental, and social challenges that impact the food security of its inhabitants, necessitating external support to reduce food vulnerability in the region.